CHALLENGES IN TRANSLATING COGNITIVE METAPHORS IN UZBEK AND ENGLISH - Gayvullayeva Jasmina (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article explores the intricacies involved in translating cognitive metaphors from English into Uzbek and vice versa. Cognitive metaphors, deeply rooted in cultural, historical, and experiential domains, often defy direct translation due to differences in conceptual framing. The study draws from cognitive linguistics and translation theory to examine metaphor types, cultural models, and conceptual mappings that underlie metaphorical expressions. Through comparative examples, the article highlights common issues such as semantic loss, cultural mismatch, and lack of equivalence, and proposes strategies for preserving conceptual integrity in translation. Emphasis is placed on culturally-loaded metaphors such as "time is money," "argument is war," and "life is a journey." The findings stress the importance of cognitive awareness and cultural competence in metaphor translation.